Percutaneous Pulmonary Embolism Thrombectomy and Thrombolysis: Technical Tips and Tricks - Devcic, Zlatko; Kuo, William T. (Seminars in Interventional Radiology, 2018)
Catheter-directed therapy (CDT) is now acknowledged as a treatment option for select patients with acute massive or submassive pulmonary embolism (PE), and more patients are being considered for CDT if there is available expertise. Therefore, interventionalists should be aware of the variety of catheter-based treatment options, specific pitfalls to avoid during therapy, and the appropriate treatment endpoints. This article reviews currently available techniques and protocols for treating acute massive and submassive PE, with tips to safely and successfully perform percutaneous PE interventions.
Keywords: Pulmonary Embolism; catheter; thrombolysis; thrombectomy; interventional radiology